Chiral separation of flurbiprofen enantiomers by preparative and simulated moving bed chromatography - Ribeiro, António E. (2011)
This study presents the chiral resolution of flurbiprofen enantiomers by preparative liquid chromatography using the simulated moving bed (SMB) technology. Flurbiprofen enantiomers are widely used as nonsteroidal anti-inflammatory drugs, and although demonstrate different therapeutic actions, they are still marketed as a racemic mixture. The results presented here clearly show the importance of the selection of the proper solvent composition for the preparative separation of flurbiprofen enantiomers. Chiral SMB separation is carried out using a laboratory-scale unit (the FlexSMB-LSRE1) with six columns, packed with the Chiralpak AD1 stationary phase (20 lm). Results presented include the experimental measurement of equilibrium and kinetic data for two very different solvent compositions, a traditional high hydrocarbon content [10%ethanol/90%n-hexane/0.01% trifluoroacetic acid (TFA)] and a strong polar organic composition (100%ethanol/0.01%TFA). Experimental data, obtained using the two mobile phase compositions, are used to predict and optimize the SMB operation. After selecting 10%ethanol/90%n-hexane/0.01%TFA as the most appropriate solvent composition, three feed concentrations of racemic flurbiprofen were considered. Using 40 g/l of racemic flurbiprofen feed solution, the purities for both outlet streams were above 99.4%, the productivity was 13.1 gfeed/(Lbed h), and a solvent consumption of 0.41 Lsolvent/gfeed was achieved.